TEKNOLOGI PEMBUATAN KERUPUK BERBASIS SINGKONG DI POSDAYA MUSLIMATAN AR-RAHMAN DESA CANDIJATI KABUPATEN JEMBER DALAM UPAYA PENGENTASAN KEMISKINAN - Subroto, Gatot; Handoyo, Tri; Arum, Ayu Puspita (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2022)
This activity aims to foster and improve the welfare conditions of the community, through empowering women in the village to increase family income. This method involves counseling production of cassava crackers, introduction as well as providing production equipment and counseling about the economy and small business of production of hygienic cassava crackers certified P-IRT. The conclusions of this activity are: (1) training the production of cassava crackers using the appropriate technology of boilers to increase income, welfare of group members, and open new job opportunities. (2) Hygienic cassava crackers products was produced more hygienic with good packaging (3) Increasing the production of cassava crackers from 20 to 50 packs.